An Emergent Discriminative Learning Is Elicited During Multifrequency Testing - Zhang, Xingui; Ye, Xianhua; Cheng, Rui; Li, Qi; Xiao, Zhongju (Frontiers in Neuroscience, 2019)
In auditory-conditioned fear learning, the freezing response is independent of the sound frequencies used, but the frequency of the conditioned sound is considered distinct from those of unrelated sounds based on electrophysiological responses in the auditory system. Whether an emergent discriminative learning underlies auditory fear conditioning and which nuclei and pathways are involved in it remain unclear. Using behavioral and electrophysiological assays, we found that the response of medial prefrontal cortex (mPFC) neurons to a conditioned auditory stimulus (CS) was enhanced relative to the response to unrelated frequencies (UFs) after auditory fear conditioning, and mice could distinguish the CS during multifrequency testing, a phenomenon called emergent discriminative learning. After silencing the mPFC with muscimol, emergent discriminative learning was blocked. In addition, the pure tone responses of mPFC neurons were inhibited after injection of lidocaine in the ipsilateral primary auditory cortex (A1), and the emergent discriminative learning was blocked by silencing both sides of A1 with muscimol. This study, therefore, provides evidence for an emergent discriminative learning mediated by mPFC and A1 neurons after auditory fear conditioning.